2007
DOI: 10.1038/sj.leu.2404532
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing Tel-FLT3, a constitutively activated form of FLT3, develop myeloproliferative disease

Abstract: Evidence is continuing to accumulate that the FMS-like tyrosine kinase 3 (FLT3) receptor plays an important role in acute leukemias. Acute myeloid leukemia patients often express constitutive active mutant forms of the receptor in their leukemic cells. A t(12;13)(p13;q12) translocation between Tel and the FLT3 receptor was recently described in a patient with myeloproliferative disease (MPD). Here a Tel-FLT3 construct mimicking this fusion protein was used to generate transgenic mice. The fusion protein was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…Additional experiments confirmed the transforming properties of the ETV6-FLT3 fusion protein in Ba/F3 cells and mice. 5,6 Grand et al 7 reported a female patient with atypical chronic myeloid leukemia (CML) and an SPTBN1-FLT3 fusion who achieved long-term remission after receiving an allograft. SPTBN1-FLT3-transformed Ba/F3 cells were sensitive to several FLT3 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Additional experiments confirmed the transforming properties of the ETV6-FLT3 fusion protein in Ba/F3 cells and mice. 5,6 Grand et al 7 reported a female patient with atypical chronic myeloid leukemia (CML) and an SPTBN1-FLT3 fusion who achieved long-term remission after receiving an allograft. SPTBN1-FLT3-transformed Ba/F3 cells were sensitive to several FLT3 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the number of CFU-GM, BFU-E, CFU-S and CFU-GEMM was produced. Mice developed MPD with a high incidence but did not succombed to leukemia (Baldwin et al, 2007).…”
Section: Leukaemia Section Mini Reviewmentioning
confidence: 99%
“…Following this report, transgenic mice expressing ETV6-FLT3 were used (Baldwin et al, 2007). Expression of the fusion protein in the transgenic mice was found in spleen, bone marrow, thymus, and liver.…”
Section: Leukaemia Section Mini Reviewmentioning
confidence: 99%
“…Following the first report, transgenic mice expressing ETV6-FLT3 were used (Baldwin et al, 2007). Expression of the fusion protein in the transgenic mice was found in spleen, bone marrow, thymus, and liver.…”
Section: Notementioning
confidence: 99%
“…A significant increase in the number of CFU-GM, BFU-E, CFU-S and CFU-GEMM was produced. Mice developed MPD with a high incidence but did not succumbed to leukemia (Baldwin et al, 2007).…”
Section: Notementioning
confidence: 99%